Assessing the Sustainable Fishery-based Industry in Malaysia Using the Analytic Hierarchy Process (AHP). Issue 1 (May 2020) - Awang, A; Wan Mohd, W R; Abdullah, L; Lee, S T
Abstract: The concept of sustainability in the fishing-based industry is to reach and maintain the fishery at the maximum sustainable yield. This principle is important to ensure that the population of fish is maintained without compromising the ability of the future generations to meet their own needs. Inefficient sustainable management could cause the depletion of natural resources, pollutions and natural habitat loss in the future. Therefore, a good sustainable management for fishery should be emphasized so that future generations can enjoy what we have today. However, the fishery management is characterized by multiple conflicting attributes which are complicated to be inspected. In this paper, we would like to investigate the fishery management problem analytically by using the Analytic Hierarchy Process (AHP) method. Considering four criteria and thirteen sub-criteria influencing to the sustainability in the fishery-based industry, the AHP method will analyse and prioritize each criterion and sub-criterion. The BPMSG AHP Online System is used as the tool to process the collected data and the final results show that the protected species interaction (PSI) is the most important sub-criteria towards achieving the sustainable fisheries. This followed by the sub-criteria of profit (14.2%), employment (10.9%) and overfishing (8.90%). These four top sub-criteria must be monitored regularly as it can influence the sustainability of fishery-based industry. The other sub-criteria have their own priorities which should not be neglected as well.